Produção in vitro de embriões (PIVE) na bovinocultura de leite e de corte - João Gabriel Viana de Grázia (2019)
The Brazilian cattle herd is the second largest in the world in number of individual, being mostly composed of commercial animals. The Nellore breed forms the basis of this herd and stands out for its good oocyte and blastocyst production in the in vitro environment. The elite herds were largely responsible for the success of IVEP in the early 2000s. On the other hand, dairy cattle make a significant contribution to the total number of embryos produced in Brazil. Among the main dairy breeds, the Gir breed (Bos indicus) and the Holstein breed (Bos taurus) stand out and their importance in the production of crossbred animals. On the other hand, the production of in vitro embryos destined for commercial beef herds is still very incipient. To this end, researches are important to better understand the factors that affect outcomes, from oocyte collection to animal birth in order to improve process efficiency and reduce costs. Mainly from the observed gestational losses of in vitro produced embryos. Therefore, the aim of this study was to understand the role of the oocyte donor in IVEP result variations and to identify and understand sources of IVEP result variation and embryo transfer. We used the database of two commercial labs, one focused on dairy cattle and another focused on beef cattle. Given the non-normality, the SAS GLIMMIX statistical model (SAS University Edition; SAS Institute Inc., Cary, NC, USA) was applied. Results are presented as mean ± standard error and was considered P <0.05. There is a wide range of results depending on the bull used, but blastocyst rates are higher when the oocyte is obtained from a Gir female, independent of the bull breed (HolsteinXHolstein: 36.4%; GirXGir: 59.2%; HolsteinXGir : 40.4%; GirXHolstein: 50.0%; p <0.05). Motility was the only sperm parameter that correlated with blastocyst production (R = 0.47 and P = 0.0002). Effect of IVM medium and IVC atmosphere on blastocyst rate was observed, while IVM system and semen preparation method had no effect. Of the various variables analyzed related to embryo transfer, the main effect observed on pregnancy rates and gestational losses was the embryo development stage (Bi: 32.0%, 28.9%, 4.1%; Bl: 34, 1%, 27.4%, 65%; Bx: 39.9%, 33.4%, 10.6%; Be: 29.3%, 22.4%, 10.3%; for P30, P60 and abortion respectively) while for birth and gestational losses were the month of the breeding season (1: 6.9%, 21.4%; 2: 16.9%, 14.5%; 3: 28.3%, 5 4: 26.9%, 9.3%; 5: 25.5%, 4.6%; 6: 21.6%, 9.0%; for Parturition and abortion respectively). In conclusion, the contribution of the oocyte donor to IVEP results is more significant than the semen used. As for ET, the influence of the laboratory on the results is smaller than the influence of field related variables.